Correction: Jahn-Teller distortion and dissociation of CCl4+ by transient X-ray spectroscopy simultaneously at the carbon K- and chlorine L-edge. Issue 35 (24th August 2022) - Ross, Andrew D.; Hait, Diptarka; Scutelnic, Valeriu; Haugen, Eric A.; Ridente, Enrico; Balkew, Mikias B.; Neumark, Daniel M.; Head-Gordon, Martin; Leone, Stephen R.
Abstract : Correction for 'Jahn-Teller distortion and dissociation of CCl4 + by transient X-ray spectroscopy simultaneously at the carbon K- and chlorine L-edge' by Andrew D. Ross et al., Chem. Sci., 2022, ; https://doi.org/10.1039/d2sc02402k .